1997
DOI: 10.1177/1420326x9700600103
|View full text |Cite
|
Sign up to set email alerts
|

The Specificity of trans,trans- Muconic Acid as a Biological Indicator for Low Levels of Environmental Benzene

Abstract: trans, trans -Muconic acid (MA), a urinary ring-opened metabolite of benzene, is a newly proposed biological indicator of benzene exposure which should enable the assessment of low levels of exposure to this ubiquitous environmen tal pollutant. The presence of MA in the urine of non-occupationally exposed people is generally attributed to world-wide contamination of the environ ment by benzene (arising from such sources as smoking and other combustion, urban pollution from vehicles and maybe by food contaminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…A number of recent publications (Pezzagno and Maestri 1997;Renner et al 1999;Weaver et al 2000) has shown that at lower exposure levels the use of TTMA as a biomarker is complicated by the fact that it is also a metabolite of the food preservative, sorbic acid (SA). SA itself (the commercial product being the trans,trans-isomer) (E 200) and its salts: sodium (E 201), potassium (E 202), and calcium (E 203) sorbate have become the most commonly used preservatives in the food industry throughout the world over the past 30 years (Luck 1990).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of recent publications (Pezzagno and Maestri 1997;Renner et al 1999;Weaver et al 2000) has shown that at lower exposure levels the use of TTMA as a biomarker is complicated by the fact that it is also a metabolite of the food preservative, sorbic acid (SA). SA itself (the commercial product being the trans,trans-isomer) (E 200) and its salts: sodium (E 201), potassium (E 202), and calcium (E 203) sorbate have become the most commonly used preservatives in the food industry throughout the world over the past 30 years (Luck 1990).…”
Section: Discussionmentioning
confidence: 99%
“…If so, the specificity of TTMA as a biological indicator of benzene exposure assessment is in doubt. The special investigation by Pezzagno and Maestri (1997) shows that more than 75% of the TTMA of food origin is excreted within 6 h of ingestion. In order to avoid any confusion related to SA ingestion, all workers were advised 12 h before the investigation not to consume foods containing SA as an additive or anti-microbial agent: canned food (meat, fish), food emulsions (such as mayonnaise and salad dressings) and various beverages with SA content marked on the label.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the International Program on Chemical Safety in 1993 reported that about 60% of workers are exposed to benzene at levels lower than 0.1 ppm and only 1% of them are exposed to levels higher than 10 ppm [1], workers in different industries and workplaces are among the higher-risk groups exposed to benzene.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas MA is not wholly specific (Vinci et al, 2012;Seow et al, 2012;Protano et al, 2010;Hoet Contents et al, 2009;Johnson et al, 2007;Weaver et al, 2000), S-PMA is a specific biological marker of benzene exposure (Tong et al, 2013;Seow et al, 2012;Hoet et al, 2009;Klauning and Kamendulis, 2004;Weaver et al, 2000;Pezzagno and Maestri, 1997), because it is unaffected by known confounding factors (Mandani et al, 2013;Fustinoni et al, 2012;Johnson et al, 2007;La Rocca et al, 2002;Pezzagno and Maestri, 1997).…”
Section: Introductionmentioning
confidence: 99%